Cardiac metastases. Issue 1 (10th November 2006) - Bussani, R; De-Giorgio, F; Abbate, A; Silvestri, F
Abstract : Tumours metastatic to the heart (cardiac metastases) are among the least known and highly debated issues in oncology, and few systematic studies are devoted to this topic. Although primary cardiac tumours are extremely uncommon (various postmortem studies report rates between 0.001% and 0.28%), secondary tumours are not, and at least in theory, the heart can be metastasised by any malignant neoplasm able to spread to distant sites. In general, cardiac metastases are considered to be rare; however, when sought for, the incidence seems to be not as low as expected, ranging from 2.3% and 18.3%. Although no malignant tumours are known that diffuse preferentially to the heart, some do involve the heart more often than others—for example, melanoma and mediastinal primary tumours. This paper attempts to review the pathophysiology of cardiac metastatic disease, epidemiology and clinical presentation of cardiac metastases, and pathological characterisation of the lesions.